Methodology to quantify the efficacy of iodine thyroid blocking via Level 3 PSA to support emergency planning - Jia Hao Tang; Sung-yeop Kim (Nuclear Engineering and Technology)
Iodine thyroid blocking (ITB) is an important aspect of the emergency protective action critical in safeguarding the population from adverse health effects from radioiodine that may potentially be released in a nuclear accident. Efficacy and impact of ITB has been dependent on qualitative assessment and expert judgement. To better evaluate the influence of ITB, this study aims to provide a methodology to tap into the results from iodine biokinetic models and couple them with Level 3 PSA MACCS code. In this methodology, ITB efficacy is determined from plume exposure time data derived from Level 3 PSA and the efficacy curve from an iodine biokinetic model. As a result, acute radiation doses can be obtained to provide an informative analysis of ITB. This study also showcases three applications of the methodology to evaluate ITB distribution strategies and incorporation into emergency action plans. The results suggest that pre-distribution is preferred for the population at a close distance from the release site. It is also noted that timely activation of the ITB strategy is a critical factor in ensuring efficacy. Finally, potential improvements to emergency action plans regarding the incorporation of ITB by considering the time points of accident sequences are suggested.